The favorable role of homozygosity for killer immunoglobulin-like receptor (KIR) A haplotype in patients with advanced-stage classic Hodgkin lymphoma. Issue 1 (December 2016) - La Nasa, Giorgio; Greco, Marianna; Littera, Roberto; Oppi, Sara; Celeghini, Ivana; Caria, Rossella; Lai, Sara; Porcella, Rita; Martino, Massimo; Romano, Alessandra; Di Raimondo, Francesco; Gallamini, Andrea; et al.
Abstract Background Interim positron emission tomography after 2 cycles of ABVD (iPET-2) is a good predictor of outcome in advanced-stage classic Hodgkin lymphoma. So far, there are no other prognostic biomarkers capable of identifying chemotherapy refractory patients with comparable accuracy. Despite the considerable amount of evidence suggesting that antitumor immune surveillance is downregulated in classic Hodgkin lymphoma (cHL), few data exist on the impairment of natural killer cell function and the role of their killer immunoglobulin-like receptors (KIRs). Methods We investigated KIR gene frequencies, KIR haplotypes, and KIR-ligand combinations in a cohort of 135 patients with advanced-stage classic Hodgkin lymphoma and 221 healthy controls. We furthermore evaluated the correlation of KIR genes and KIR haplotypes with the achievement of negative iPET-2. Results In the cohort of patients, the 5-year overall survival and progression-free survival were 93.6 and 79 %, respectively. Homozygosity for KIR A haplotype and the HLA-C1 KIR ligand (KIR-AA/C1C1) was significantly higher in healthy controls (15.7 vs. 4.8 %, p  = 0.001). The KIR-AA genotype resulted to have a significant predictive power for achieving iPET-2 negativity (p  = 0.039). Conclusions Homozygosity for KIR A haplotype offers protection against classic Hodgkin lymphoma. The association found for the KIR-AA genotype and achievement of negative iPET-2 suggests that KIR-AA could be used in clinical practice to enhance the chemosensitivity predictive power of iPET-2. Our results point to the possibility of adapting treatment strategies based on the combination of KIR biomarkers and PET scan.